Navigating the Hospitality Industry: Barriers and Career Choices of Female Managers in Sweden - Nuñez,Natalia; Pestic,Anamaria (2025)
While women comprise the majority of the hospitality industry workforce, making 56% in the EU market, they still remain significantly underrepresented in leadership roles, with 38% in top-level roles and less than 40% in managerial positions. This gender gap is evident in the Swedish hospitality sector where the higher volume of women are concentrated in part-time roles with a lower pay and facing organizational and systematic barriers that hinder them from progressing in their professional careers. This study focuses on exploring the barriers women in managerial positions face in advancing and/or sustaining their careers in the hospitality industry and also aims to uncover the career choices and strategies they follow to remain relevant and successful. This study adopted an interpretivist approach to understand the experiences of women in hospitality management, following an abductive qualitative research that allowed iterating back and forth between theory and emergent data. The study employed purposive and snowball sampling to identify female managers in the industry with relevant career experiences. We conducted six semi structured interviews with mid and top level female managers and followed a six phase thematic analysis grounded in theory and empirical data to analyze them. The analysis revealed five main themes: Gender expectations and identity in management, Support structures and development, Evolving management styles, Work-life balance and wellbeing, Self awareness and personal development.
Keywords: Success strategies; tourism and hospitality management; female leadership; gender equality; gender barriers; industry strategy implications